Gamification as a Strategy to Improve Student Learning Motivation : Preparing Student for 21st Century - Barokati Seliro Wangi, Nisaul; Setyosari, Punaji; Kuswandi, Dedi; D Dwiyogo, Wasis (International Journal of Engineering and Technology, 2018)
The development of digital technology is so fast where human beings cannot be separated from electronic devices. Technology has been used to help doing the task and work easily. The important role of technology is what brings human to civilization in the 21st century. To prepare students, we try to create new research related to gamification based learning that basically can be done anytime and anywhere. It is useful to improve the spirit and sense of fun in learning, so that students who have high learning motivation have a lot of energy to carry out learning activities and can obtain high learning outcomes. The use of gamification based learning strategy brings significant differences compared with conventional learning strategies in term of learning outcomes. There are differences in learning outcomes between groups of students who have high learning motivation and groups of students who have low learning motivationÂ Â